1998
DOI: 10.7326/0003-4819-129-10-199811150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Dietary Intake of Vitamin A Is Associated with Reduced Bone Mineral Density and Increased Risk for Hip Fracture

Abstract: High dietary intake of retinol seems to be associated with osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
222
2
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(237 citation statements)
references
References 35 publications
5
222
2
7
Order By: Relevance
“…Addition of 9cRA to 1,25D treatment completely prevented the weight loss and kidney calcification seen with 1,25D treatment alone, without decreasing the effectiveness of 1,25D treatment against lung tumor incidence and multiplicity. An effect of retinoids on calcium homeostasis has been shown more clearly in studies investigating the association between vitamin A and fracture risk, [45][46][47][48] and the influence of retinoids on vitamin D regulation of serum calcium and bone mineral homeostasis. 35,49,50 Unfortunately, we were unable to obtain sufficient data to report serum or urine calcium levels in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of 9cRA to 1,25D treatment completely prevented the weight loss and kidney calcification seen with 1,25D treatment alone, without decreasing the effectiveness of 1,25D treatment against lung tumor incidence and multiplicity. An effect of retinoids on calcium homeostasis has been shown more clearly in studies investigating the association between vitamin A and fracture risk, [45][46][47][48] and the influence of retinoids on vitamin D regulation of serum calcium and bone mineral homeostasis. 35,49,50 Unfortunately, we were unable to obtain sufficient data to report serum or urine calcium levels in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Melhus and cols. (30) showed that excessive vitamin A supply associates negatively with BMD, even after adjustments in the other risk factors for osteoporosis. Experimental studies showed that vitamin A deficiency Arch Endocrinol Metab.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chemotherapy, corticosteroids and retinoids received during induction and salvage therapy can decrease bone mineral density. [10][11][12][13] Furthermore, multiple myeloma is associated with systemic osteoporosis as a result of increased osteoclastic activity. 14 ABMT patients also may have general risk factors for osteoporosis that include older age, 15 thin body habitus, 16,17 a family history of osteoporosis, 18 smoking, 19,20 and physical inactivity.…”
mentioning
confidence: 99%